“MENJEMPUT KERINDUAN KELUARGA” PENYELESAIAN DAN PENGEMBALIAN TAHANAN POLITIK PULAU BURU KE MASYARAKAT, 1965-1979 - Sarkawi B. Husain (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
One of the further effects of the G30S was the arrest of thousands of people who were considered PKI sympathizers. Most of them were banished and exiled to Buru Island. However, in December 1977 repatriation began. One of the main problems faced by former political prisoners was their acceptance by their families and communities. When they had to work to support their families, they often found obstacles. This paper looks at the processes political prisoners had to go through, from their arrest, banishment in Buru Island, and it also looks at the repatriation process and the difficult circumstances they had to face once they returned. Keywords: Political Prisoners, PKI, Buru Island